The decline of the exchange rate pass-through in Brazil: Explaining the "fear of floating" - Carlos Eduardo Schönerwald da Silva; Matías Vernengo (The University of Utah, Department of Economics, 2008)
This paper argues that the pass-through in Brazil has fallen compared with estimates in other studies on earlier time periods, and remains low. Whereas pass-through effects where high and close to 1 in the high-inflation period, they seem to have fallen to around 0.2 after the Real Plan stabilization, a number that is similar to the Import Substitution Industrialization (ISI) period of the 1950s and 1960s. Conventional results suggests that low and stable inflation environments lead to low levels of exchange rate pass-through and thus contribute to weakening the 'fear of floating' phenomenon experienced by some developing countries. In spite of lower pass-through effects the Brazilian Central Bank has maintained high interest rates in order to control the exchange rate. This paper suggests that 'fear of inflation' provides justification for the central bank's persistent 'fear of floating.'
Keywords: E58; F41; O54; 330; Pass-Through; Inflation; Brazil; Exchange Rate Pass-Through; Inflation; Flexibler Wechselkurs; Brasilien